Two new species of Exidia sensu lato (Auriculariales, Basidiomycota) based on morphology and DNA sequences - Tohtirjap, Ablat; Hou, Shi-Xing; Rivoire, Bernard; Gates, Genevieve; Wu, Fang; Dai, Yu-Cheng (Frontiers in Microbiology, 2023)
In the present study, fourteen Exidia-like specimens were collected from China, France, and Australia. Based on morphological characteristics and phylogenetic analyses using the internal transcribed spacer regions (ITS) and the large subunit of nuclear ribosomal RNA gene (nLSU), four species in Exidia sensu lato, including Exidia saccharina and Tremellochaete atlantica, and two new species, Exidia subsaccharina and Tremellochaete australiensis, were identified. The four species are described and illustrated in detail. E. saccharina and T. atlantica, two known species from China are reported for the first time. E. subsaccharina and T. australiensis, two new species from France and Australia, respectively are also described. E. subsaccharina is characterized by its reddish brown to vinaceous brown basidiomata, slightly papillate hymenial surface, and narrowly allantoid basidiospores without oil drop measuring 12.5–17.5 × 4.2–5.5 μm. It differs from the similar species, E. saccharina, by distinctly larger basidiospores (12.5–17.5 × 4.2–5.5 vs. 10–14.2 × 3.2–4.5 μm). Tremellochaete australiensis is characterized by its white to grayish blue basidiomata, obviously and densely papillate hymenial surface, and allantoid basidiospores with oil drop measuring 13.8–16.2 × 4.8–6.5 μm. It also can be distinguished from the similar species, T. atlantica and T. japonica, by its distinctly larger basidiospores (13.5–17.8 × 4–5.2 vs. 10–11.8 × 4–4.8 μm in T. atlantica; 9.4–11.8 × 3.5–4.2 μm in T. japonica).